Deep level transient spectroscopy study of the damage induced in n-type silicon by a gate oxide etching in a CHF3/Ar plasma - Adegboyega, G.; Perez, I.V; Poggi, Antonella; Susi, E (Journal of vacuum science & technology B, 2020)
International Journal of vacuum science & technology B 15(3):623 - 628